Efficacious fungicidal potential of composite derived from nano-aggregates of Cu-Diclofenac complexes and ZnO nanoparticles. (December 2018) - Kumar, Krishan; Shyamlal, Bharti Rajesh Kumar; Gupta, Aarohi; Mathur, Manas; Swami, Ajit K.; Chaudhary, Sandeep
Abstract: The composite-based formulations have appeared as prominent " antimicrobial materials " because it provide superior antimicrobial efficacy than single component based therapeutic formulations. Herein, we report the synergistically enhanced antifungal activity of the composite developed from self-assembled nano-aggregates of copper complexes of non-steroidal anti-inflammatory drug, diclofenac (Cu-Dc) in combination with zinc oxide (ZnO) nanoparticles. The composites (ZnO-Cu-Dc) were prepared at different weight ratios (Cu-Dc/ZnO; 1:0.125–1:2) and characterized thoroughly by means of transmission electron microscopy (TEM), scanning electron microscopy (SEM), atomic force microscopy (AFM), fourier-transform infrared spectroscopy (FT-IR) and dynamic light scattering (DLS) measurements which revealed them to be nanostructured aggregates. The composite mediated treatments showed substantially increased zones of inhibition in agar well-diffusion method against a human pathogenic fungus ( Candida albicans ) and three plant pathogenic fungi ( Penicillium funiculosum, Aspergillus niger and Fusarium oxysporum ). Notably, the individual treatments using the respective concentrations of ZnO nanoparticles did not show any inhibitory activity against all the fungal strains. Optical density measurements profiled maximum reduction in fungal growth for composite treatment when compared to that of ZnO nanoparticles and Cu-Dc complexes alone. The morphological analysis of fungal cell growth by SEM and optical microscopic studies evidenced maximum deformation of biofilm mass for composite mediated treatment. Concisely, the ZnO-Cu-Dc, a composite system has been developed which can be utilized as an effective formulation against fungal infections. Highlights: Composite-based formulation has been developed as prominent " antifungal material ". ZnO-Cu- Diclofenac composite is nano-structured aggregates. Composite shows synergistic antifungal activity in pathogenic fungi . The ZnO-Cu-Dc composite significantly degrades the fungal biomass.